"Perada App: Empowering Women's and Children's Protection During COVID-19 for a Smarter, Greener Campus" - Citrawan, Ahmad Lanang; Cahyani, Ferina Ardhi (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
The COVID-19 pandemic has heightened the vulnerability of women and children to violence, necessitating prompt and effective legal assistance. This research addresses this urgent issue by developing the Perada application, a digital platform for reporting and seeking legal consultation and assistance for victims of violence. The study is conducted by the Faculty of Law at Untirta, aligning with its vision of an integrated, smart, and green campus. The application leverages smartphone technology to provide accessible support, utilizing the expertise of faculty members and students while collaborating with the Women's and Children's Protection Agency and law enforcement. Employing the Waterfall development model, the research combines descriptive, quantitative, and inferential analyses to evaluate the app’s creation process, usability, and alignment with legal principles. This study contributes to innovative, tech-driven solutions for enhancing legal protection and underscores the role of academia in addressing societal challenges.